2013
DOI: 10.1159/000356950
|View full text |Cite
|
Sign up to set email alerts
|

Embryo Reduction in Dichorionic Triplets to Dichorionic Twins by Intrafetal Laser

Abstract: Objective: To describe a new technique for embryo reduction (ER) in dichorionic triplet (DCT) pregnancies. Methods: In 22 DCT pregnancies, ER to dichorionic twins was carried out at 11.3-13.9 weeks' gestation by ultrasound-guided laser ablation of the pelvic vessels of one of the monochorionic twins. Results: Intrafetal laser was successfully carried out in all cases, but ultrasound examination within 2 weeks of the procedure demonstrated that the co-twin had died in 11 cases and was alive in the other 11. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…We have proposed a new approach for ER of DC triplet pregnancies to DC twins by ultrasound‐guided laser ablation of the pelvic vessels of one of the monochorionic twins. In a series of 22 DC triplet pregnancies undergoing intrafetal laser, ultrasound examination within 2 weeks of the procedure demonstrated that the cotwin had died in 11 cases and was alive in the other 11; in the DC group there was one miscarriage at 23 weeks and in the other 10 cases there were two live births at a median gestational age of 35 weeks, whereas in the 11 cases in which both monochorionic fetuses died, the separate triplet was liveborn at a median gestation of 38 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…We have proposed a new approach for ER of DC triplet pregnancies to DC twins by ultrasound‐guided laser ablation of the pelvic vessels of one of the monochorionic twins. In a series of 22 DC triplet pregnancies undergoing intrafetal laser, ultrasound examination within 2 weeks of the procedure demonstrated that the cotwin had died in 11 cases and was alive in the other 11; in the DC group there was one miscarriage at 23 weeks and in the other 10 cases there were two live births at a median gestational age of 35 weeks, whereas in the 11 cases in which both monochorionic fetuses died, the separate triplet was liveborn at a median gestation of 38 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, acute haemorrhage of the surviving twin may occur soon after the death of the co-twin through placental vascular anastomoses, with consequent death or neurodevelopmental impairment [34,35]. Relatively new vascular occlusive techniques have enabled the possibility of reducing a triplet pregnancy containing MC twins to a DC twin pregnancy [3,36,37]. Some studies have reported the efficiency of this new technique in women with MC twins; however, it potentially increases the risk of technique-associated complications and the rate of intrauterine demise of the retained co-twin [3,34,36].…”
Section: Discussionmentioning
confidence: 99%
“…Relatively new vascular occlusive techniques have enabled the possibility of reducing a triplet pregnancy containing MC twins to a DC twin pregnancy [3,36,37]. Some studies have reported the efficiency of this new technique in women with MC twins; however, it potentially increases the risk of technique-associated complications and the rate of intrauterine demise of the retained co-twin [3,34,36]. Chaveeva P et al [38] reported 61 DC triplet pregnancies that were reduced to DC twin pregnancies by intrafoetal laser ablation; although reduction resulted in a relatively lower miscarriage rate (3%), 45.9% of the cases of co-twin miscarriage within the subsequent 2 weeks were likely due to incomplete vascular occlusion and 9 retrograde haemorrhage of the survivor through placental vascular anastomoses into the dead cotwin.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, reduction to two fetuses by reducing one of the monochorionic pair and retaining dichorionic twins has been proposed [23,24]. The techniques described include aspiration of embryonic parts at 6-8 week [23] or intrafetal interstitial laser ablation at 11-14 weeks [24].…”
Section: Discussionmentioning
confidence: 99%
“…The techniques described include aspiration of embryonic parts at 6-8 week [23] or intrafetal interstitial laser ablation at 11-14 weeks [24]. The latter might be a concept, especially for complications in the monochorionic pair evident as early as in the first trimester even if the death of the monochorionic co-twin was observed in 50 % of cases 2 weeks later [24].…”
Section: Discussionmentioning
confidence: 99%